Effect of Particle Shape of Limestone Manufactured Sand and Natural Sand on Concrete. (2017) - Yamei, Huang; Lihua, Wang
Abstract: The particle shape parameters of natural sand and limestone manufactured sand were studied by the DIP method. The results showed that compared with the natural sand, the manufactured sand was more 19.0% in lengthwise ratio, less 11.5% in flatness ratio, more 0.3% in convexity ratio, more 0.2% in fulness ratio, less 19.3% in particle shape parameters, and less 14.8% in sphericity. Therefore, the natural sand was more close to sphere shape and more smooth, while the manufactured sand was more slim, flat and rough. When slump and the cement dosage are at the same time, manufactured sand concrete has larger water usage and less air content, but the compressive strength is greater than natural sand concrete.